2018
DOI: 10.1177/1078345818792055
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-Spanning Care: Reducing Psychiatric Rehospitalization and Self-Injury in a Jail Population

Abstract: Individuals with serious mental illness detained in jail may require frequent psychiatric hospitalization due to the destabilizing nature of the jail environment. This study examined the impact of a pilot treatment program involving continuity of patient care across jail and hospital settings aimed at reducing hospitalizations and negative health outcomes for a population of high-risk, incarcerated individuals with mental illness. This study examined rate ratios of psychiatric hospitalizations, injuries, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Ten studies evaluated the efficacy of psychotherapy. 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Six studies analyzed comprehensive multicomponent suicide prevention strategies. 6 , 32 , 43 , 44 , 45 , 46 Two studies reported on the efficacy of peer support schemes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies evaluated the efficacy of psychotherapy. 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Six studies analyzed comprehensive multicomponent suicide prevention strategies. 6 , 32 , 43 , 44 , 45 , 46 Two studies reported on the efficacy of peer support schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported various issues related to conducting an evaluation study in prison settings. 33 , 36 , 38 , 44 , 47 These issues included the frequent and unpredictable transfer or release of prisoners that can increase the rate of attrition. 33 Furthermore, the nature of correctional facilities can prevent researchers from carrying out randomization.…”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that COs can play an active role in the promotion of rehabilitative goals by providing encouragement and positive support and assisting in the procurement of resources and services (Schaefer, 2018; Tait, 2011). In the American criminal justice system, duties that were traditionally assigned to various correctional staff are slowly blending to other positions as ideas about the effectiveness of prison programming are changing and the need for boundary spanning 1 has become imminent in jail-to-community initiatives (Bratina, 2017; Bursac et al, 2018; Manchak et al, 2014; Rao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“… 1. Referring to a process whereby individuals who have experience working in multiple systems of care have the ability and expertise to provide cross-systems perspectives and/or multidisciplinary problem-solving strategies (Bratina, 2017; Bursac et al, 2018). …”
mentioning
confidence: 99%